1998
DOI: 10.1111/j.1440-1827.1998.tb03894.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel marker of Schwann cells and myelin of the peripheral nervous system

Abstract: Cellular markers are useful in the immunohistochemical studies of normal and pathological tissues. Herein, the development of a monoclonal antibody, Schwann/2E, which reacts with Schwann cells and myelin of the peripheral nervous system (PNS) is described. The Schwann/2E antibody was secreted by a hybridoma of mouse myeloma cells and mouse spleen cells that were immunized in vivo with a cytoskeletal fraction of the human spinal nerve. This antibody immunostained formalin-fixed, paraffin-embedded human, rat, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Fiftymicrometer-thick sections were cut on a freezing microtome and stained with either (1) luxol fast blue, (2) cresyl violet, (3) luxol fast blue with cresyl violet counterstaining (K lüver and Barrera stain), or (4) hematoxylin and eosin. Immunocytochemistry was performed according to standard protocols at antibody dilutions recommended by the manufacturer using primary antisera directed against the following: Schwann cells (Schwann /2E) (Dr. Y. Nakazato, Gunma University, Gunma, Japan) (Arai et al, 1998); protein P zero (P 0 ) (Dr. J. Archelos, Karl-Franzens-University, Graz, Austria); p75 neurotrophin receptor (p75) (Dr. L. Reichardt, University of C alifornia, San Francisco, CA); glial fibrillary acidic protein (GFAP; Roche-Boehringer, Indianapolis, I N; C lone G-A-5); oligodendrocytes (M AB1580) (Chemicon, Temecula, CA,); OX-8, San Diego,CA); ED1 (Serotec, Raleigh, NC); C TB (List Biologic, C ampbell, CA); or saporin (Advanced Targeting Systems). We found that the Schwann /2E and P 0 antibodies produced equivalent staining, and therefore both antibodies were used to identif y myelinating Schwann cells.…”
Section: Methodsmentioning
confidence: 99%
“…Fiftymicrometer-thick sections were cut on a freezing microtome and stained with either (1) luxol fast blue, (2) cresyl violet, (3) luxol fast blue with cresyl violet counterstaining (K lüver and Barrera stain), or (4) hematoxylin and eosin. Immunocytochemistry was performed according to standard protocols at antibody dilutions recommended by the manufacturer using primary antisera directed against the following: Schwann cells (Schwann /2E) (Dr. Y. Nakazato, Gunma University, Gunma, Japan) (Arai et al, 1998); protein P zero (P 0 ) (Dr. J. Archelos, Karl-Franzens-University, Graz, Austria); p75 neurotrophin receptor (p75) (Dr. L. Reichardt, University of C alifornia, San Francisco, CA); glial fibrillary acidic protein (GFAP; Roche-Boehringer, Indianapolis, I N; C lone G-A-5); oligodendrocytes (M AB1580) (Chemicon, Temecula, CA,); OX-8, San Diego,CA); ED1 (Serotec, Raleigh, NC); C TB (List Biologic, C ampbell, CA); or saporin (Advanced Targeting Systems). We found that the Schwann /2E and P 0 antibodies produced equivalent staining, and therefore both antibodies were used to identif y myelinating Schwann cells.…”
Section: Methodsmentioning
confidence: 99%
“…For research, the development and application of new diagnostic biomarkers are necessary. Our laboratory has been establishing many polyclonal and monoclonal antibodies against nervous system antigens [1,1719,2631]. We are already using some of these antibodies for routine pathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Schwann/2E was first introduced as a monoclonal antibody that reacts with Schwann cells and myelin of the peripheral nervous system . Although the staining pattern of Schwann/2E in human specimens has not been well explored yet, a previous study where immunoreactivities of S‐100 and Schwann/2E in various types of peripheral nerve tumors were examined, showed that 70 of 92 schwannomas (78 %) were positive for Schwann/2E, whereas all of six malignant schwannomas and 12 neurofibromas were negative .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report two cases of morphologically schwannoma‐like tumor in the anterior cranial fossa that was immunonegative for Leu7 but immunopositive for Schwann/2E, a marker of Schwann cells, and discuss the origin of these tumors.…”
Section: Introductionmentioning
confidence: 97%